Stress-induced sensitization of insula activation predicts alcohol craving and alcohol use in alcohol use disorder: archival report - Bach, Patrick; Zaiser, Judith; Vetter, Sina; Gessner, Tatjana; Hoffmann, Sabine; Gerhardt, Sarah; Berhe, Oksana; Bekier, Nina Kim; Abel, Martin; Radler, Philipp; Langejürgen, Jens; Tost, Heike; et al. (Biological psychiatry, 2024)
Background - Stress and alcohol cues trigger alcohol consumption and relapse in alcohol use disorder. However, the neurobiological processes underlying their interaction are not well understood. Thus, we conducted a randomized, controlled neuroimaging study to investigate the effects of psychosocial stress on neural cue reactivity and addictive behaviors. - Methods - Neural alcohol cue reactivity was assessed in 91 individuals with alcohol use disorder using a validated functional magnetic resonance imaging (fMRI) task. Activation patterns were measured twice, at baseline and during a second fMRI session, prior to which participants were assigned to psychosocial stress (experimental condition) or a matched control condition or physical exercise (control conditions). Together with fMRI data, alcohol craving and cortisol levels were assessed, and alcohol use data were collected during a 12-month follow-up. Analyses tested the effects of psychosocial stress on neural cue reactivity and associations with cortisol levels, craving, and alcohol use. - Results - Compared with both control conditions, psychosocial stress elicited higher alcohol cue-induced activation in the left anterior insula (familywise error-corrected p < .05) and a stress- and cue-specific dynamic increase in insula activation over time (F22,968 = 2.143, p = .007), which was predicted by higher cortisol levels during the experimental intervention (r = 0.310, false discovery rate-corrected p = .016). Cue-induced insula activation was positively correlated with alcohol craving during fMRI (r = 0.262, false discovery rate-corrected p = .032) and alcohol use during follow-up (r = 0.218, false discovery rate-corrected p = .046). - Conclusions - Results indicate a stress-induced sensitization of cue-induced activation in the left insula as a neurobiological correlate of the effects of psychosocial stress on alcohol craving and alcohol use in alcohol use disorder, which likely reflects changes in salience attribution and goal-directed behavior.